PYGMALION GOLD AWARD - Mouzouropoulos, Theseas (My University, 2026)
The award was received by the Creative Club of Cyprus member of the Art Directors Club of Europe (ADCE)for exemplary design and concept in the category Branding Design. The concept of the Branding designed for the ICSVC Conference is based on the multimodal nature of Typography, having two sign systems juxtaposed together for communication; the Braille and the Visual, combined with customized letter-forms for a simultaneous ‘touch-and-see’ interpretation of the message.
Keywords: Arts and entertainment